Observations on the skull of the type specimen of Tyrannosaurus rex Osborn, 1905 - Thomas D. Carr (All Earth)
The skull bones of the type specimen of Tyrannosaurus rex have been undescribed since the early 20th Century. The objectives were to provide a description of the type skull, assess the homology of characters seen in adults and juveniles, and test the taxonomic informativeness of the size difference between the second and third dentary teeth. This work is based on published data and first-hand observations of fossils and casts. Comparative descriptions of each skull bone, and details of the dentition of the type were written. Several retained ‘juvenile’ characters are not homologous with the juvenile condition. The difference in size between the second and third dentary teeth are taxonomically uninformative. Inferences were made regarding the complementary joint surfaces of the skull bones that were attached to those found in CM 9380. Both dental characters suggested to differentiate species in the hypodigm of T. rex were seen in the left and right dentaries of the type; therefore, the characters are taxonomically uninformative. The subocular process seen in the lacrimal in T. rex and other large theropods was hypothesised to mark the limit of the eyeball-containing region of the orbital fenestra.